2019
DOI: 10.3390/w11112299
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Soil Conservation and Eucalyptus on Hydrology and Soil Loss in the Ethiopian Highlands

Abstract: The Ethiopian highlands suffer from severe land degradation, including erosion. In response, the Ethiopian government has implemented soil and water conservation practices (SWCPs). At the same time, due to its economic value, the acreage of eucalyptus has expanded, with croplands and pastures converted to eucalyptus plantations. The impact of these changes on soil loss has not been investigated experimentally. The objective of this study, therefore, is to examine the impacts of these changes on stream discharg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 39 publications
3
18
0
Order By: Relevance
“…The average cumulative rainfall required for a 20 mm runoff depth increased from 371 mm in the first period before intervention to 442 mm after interventions ( Figure 10). The result agrees with the finding of another recent study from the Ethiopian Highlands [47]. Therefore, using the satellite image data of MODIS, the dry season, the month of March, evapotranspiration over the Gumara was extracted and found to be increasing between 2001 and 2019 ( Figure 9).…”
Section: Low and High Flowssupporting
confidence: 91%
See 3 more Smart Citations
“…The average cumulative rainfall required for a 20 mm runoff depth increased from 371 mm in the first period before intervention to 442 mm after interventions ( Figure 10). The result agrees with the finding of another recent study from the Ethiopian Highlands [47]. Therefore, using the satellite image data of MODIS, the dry season, the month of March, evapotranspiration over the Gumara was extracted and found to be increasing between 2001 and 2019 ( Figure 9).…”
Section: Low and High Flowssupporting
confidence: 91%
“…studies in lake Tana Basin [46]. In addition, a study on the hydrological impact of a Eucalyptus plantation found that the cumulative rainfall required to generate 3 mm runoff was higher after a threefold expansion of the plantation area [47].…”
Section: Low and High Flowsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another clear example of human disturbance is the research published by Mhiret et al [14] about land degradation and soil conservation measures carried out to reduce soil loss in the Ethiopian Highlands. This territory suffers from severe land degradation, including erosion, and in response, the Ethiopian government has implemented soil and water conservation practices considering the acreage of eucalyptus, which has been expanded.…”
Section: Summary Of This Special Issuementioning
confidence: 99%